Simplified modeling of implanted medical devices with metallic filamentary closed loops exposed to low or medium frequency magnetic fields. (February 2023) - Bottauscio, Oriano; Arduino, Alessandro; Chiampi, Mario; Zilberti, Luca
Highlights: A numerical methodology to efficiently model implanted medical devices with metallic filamentary closed loops exposed to low or medium frequency magnetic fields was presented. The methodology is validated against a test case, with errors in the amplitude of the currents induced in the closed wires always lower than 3%, and compared with a commercially available software. It is proved the applicability of the methodology to a number of realistic exposure scenarios in presence of a skull grid. This modeling tool allows analyzing different types of small implants, from coronary and biliary duct stents to orthopedic grids, under a variety of exposure scenarios. Abstract: Background and objectives: Electric currents are induced in implanted medical devices with metallic filamentary closed loops (e.g., fixation grids, stents) when exposed to time varying magnetic fields, as those generated during certain diagnostic and therapeutic biomedical treatments. A simplified methodology to efficiently compute these currents, to estimate the altered electromagnetic field distribution in the biological tissues and to assess the consequent biological effects is proposed for low or medium frequency fields. Methods: The proposed methodology is based on decoupling the handling of the filamentary wire and the anatomical body. To do this, a circuital solution is adopted to study the metallic filamentary implant and this solution is inserted in the electromagnetic field solution involving the biological tissues. The Joule losses computed in the implant are then used as a forcing term for the thermal problem defined by the bioheat Pennes' equation. The methodology is validated against a model problem, where a reference solution is available. Results: The proposed simplified methodology is proved to be in good agreement with solutions provided by alternative approaches. In particular, errors in the amplitude of the currents induced in the wires result to be always lower than 3%. After the validation, the methodology is applied to check the interactions between the magnetic field generated by different biomedical devices and a skull grid, which represents a complex filamentary wire implant. Conclusions: The proposed simplified methodology, suitable to be applied to closed loop wires in the low to intermediate frequency range, is found to be sufficiently accurate and easy to apply in realistic exposure scenarios. This modeling tool allows analyzing different types of small implants, from coronary and biliary duct stents to orthopedic grids, under a variety of exposure scenarios.